PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN IPS KELAS VII A - Darmayanti, Sayu; Adi, Khofifatu Rohmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low student motivation remains a challenge in Social Studies (IPS) learning, particularly in class VII A of SMP Negeri 22 Malang. Conventional teacher-centered methods tend to limit student engagement and participation. This study aims to improve students' learning motivation by implementing the discovery learning model. The research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through student motivation questionnaires, observation sheets filled out by the supervising teacher, and documentation during the learning process. The data were analyzed using descriptive quantitative and qualitative approaches. The results showed a gradual increase in students' motivation across the research cycles. In the pre-cycle stage, the average motivation score was 41.3, categorized as low. After applying the discovery learning model in cycle I, the average score increased to 50.6, categorized as high. In cycle II, the score further improved to 58.3, remaining in the high category. Besides score improvements, students also demonstrated more active participation in discussions, greater independence, and increased confidence in expressing their ideas.